PENGARUH BRAND IMAGE, COUNTRY OF ORIGIN DAN PERCEIVED QUALITY TERHADAP PURCHASE INTENTION SMARTPHONE: STUDI PADA PENGGUNA DI DKI JAKARTA - Dewi Linda Sari; Nadya Fadillah Fidyallah; Dewi Agustin Pratama Sari (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
Abstract. This study aims to analyze the influence of Brand Image, Country of Origin, and Perceived Quality on Purchase Intention of smartphones, with a case study on users in Jakarta. The research is motivated by the growing competition among smartphone brands and the importance of consumer perception in terms of brand image, product origin, and perceived quality in shaping buying intentions. A quantitative approach was employed using a survey method. Data were collected through an online questionnaire distributed to 150 smartphone users in Jakarta. The data were analyzed using multiple linear regression to examine the relationships between variables. The results reveal that Brand Image and Perceived Quality have a positive and significant influence on Purchase Intention, while Country of Origin does not have a significant effect. These findings imply that companies should focus on strengthening brand image and enhancing perceived product quality in their marketing strategies. Keywords: Brand Image, Country of Origin, Perceived Quality, Purchase Intention, Smartphone Abstrak. Penelitian ini bertujuan untuk menganalisis pengaruh Brand Image, Country of Origin, dan Perceived Quality terhadap Purchase Intention smartphone dengan studi kasus pada pengguna di Jakarta. Latar belakang penelitian ini didasari oleh meningkatnya persaingan merek smartphone serta pentingnya persepsi konsumen terhadap citra merek, asal negara produk, dan kualitas yang dirasakan dalam mempengaruhi niat beli. Penelitian ini menggunakan pendekatan kuantitatif dengan metode survei. Data dikumpulkan melalui kuesioner online yang disebarkan kepada 150 responden pengguna smartphone di Jakarta. Teknik analisis data yang digunakan adalah regresi linear berganda untuk menguji hubungan antar variabel. Hasil penelitian menunjukkan bahwa Brand Image dan Perceived Quality berpengaruh positif dan signifikan terhadap Purchase Intention, sedangkan Country of Origin tidak berpengaruh signifikan. Temuan ini memberikan implikasi bagi perusahaan dalam merancang strategi pemasaran yang berfokus pada penguatan citra merek dan peningkatan persepsi kualitas produk. Kata kunci: Brand Image, Country of Origin, Perceived Quality, Purchase Intention, Smartphone